BEYOND THE PERIMETER: ASSESSING THE IMPACT OF ZERO TRUST ARCHITECTURE ON NETWORK LATENCY AND SECURITY RESILIENCE IN LARGE-SCALE ENTERPRISE ENVIRONMENTS - Hadi Mardiyanto; Zainal Syahlan; Isnadi Isnadi; Safiullah Aziz (Journal of Computer Science Advancements, 2026)
Enterprise networks increasingly confront sophisticated cyber threats and complex operational demands, rendering traditional perimeter-based security models inadequate. Zero Trust Architecture (ZTA) has emerged as a paradigm that emphasizes continuous verification, granular access control, and micro-segmentation to enhance security resilience across hybrid and large-scale environments. This study investigates the dual impact of ZTA on network latency and security outcomes, providing empirical insights into performance-security trade-offs.The research aims to evaluate how ZTA implementation affects network latency, throughput, and packet integrity while quantifying improvements in security resilience, including reductions in unauthorized access and lateral threat propagation. Insights from this study are intended to inform enterprise decision-making regarding optimized ZTA deployment. A mixed-methods approach was employed, combining quantitative measurements of latency, throughput, and packet loss across six enterprise networks with qualitative security assessments, including penetration testing and attack simulations. Data were analyzed using statistical techniques and thematic evaluation to identify patterns and interdependencies. Findings indicate that ZTA increases network latency moderately (3–7 ms) and reduces throughput minimally, while significantly enhancing security resilience, with a 70–85% reduction in successful unauthorized access attempts. Correlation analysis reveals a positive trade-off between performance impact and security improvements, emphasizing the importance of configuration optimization. Results confirm that ZTA provides robust protection without critically impairing network performance, offering practical guidance for large-scale enterprise adoption and informing future security-policy strategies.